Prognostic significance of ankle brachial pressure index: A systematic review and meta-analysis. (April 2017) - Hajibandeh, Shahab; Hajibandeh, Shahin; Shah, Sohan; Child, Emma; Antoniou, George A; Torella, Francesco
Purpose: To synthesize and quantify the excess risk of morbidity and mortality in individuals with low ankle-brachial pressure index. Methods: Electronic databases were searched to identify studies investigating morbidity and mortality outcomes in individuals undergoing ankle-brachial pressure index measurement. Meta-analysis of the outcomes was performed using fixed- or random-effects models. Uncertainties related to varying follow-up periods among the studies were resolved by meta-analysis of time-to-event outcomes. Results: Forty-three observational cohort studies, enrolling 94, 254 participants, were selected. A low ankle-brachial pressure index (<0.9) was associated with a significant risk of all-cause mortality (risk ratio: 2.52, 95% CI 2.26–2.82, P  < 0.00001); cardiovascular mortality (risk ratio: 2.94, 95% CI 2.72–3.18, P  < 0.00001); cerebrovascular event (risk ratio: 2.17, 95% CI 1.90–2.47, P  < 0.00001); myocardial infarction (risk ratio: 2.28, 95% CI 2.07–2.51, P  < 0.00001); fatal myocardial infarction (risk ratio: 2.81, 95% CI 2.33–3.40, P  < 0.00001); fatal stroke (risk ratio: 2.28, 95% CI 1.80–2.89, P  < 0.00001); and the composite of myocardial infarction, stroke, and death (risk ratio: 2.29, 95% CI 1.87–2.81, P  < 0.00001). Similar findings resulted from analyses of individuals with asymptomatic PAD, individuals with cardiovascular or cerebrovascular co-morbidity, and patients with diabetes. Conclusions: A low ankle-brachial pressure index is associated with an increased risk of subsequent cardiovascular and cerebrovascular morbidity and mortality. Randomised controlled trials are required to investigate the effectiveness of screening for PAD in asymptomatic and undiagnosed individuals and to evaluate benefits of early treatment of screen-detected PAD.